Hubungan Status Gizi dengan Kejadian Diare pada Anak di Desa Rantau Benuang Kabupaten Rokan Hilir - Kusyanti, Titi; Syahda, Syukrianti; Handayani, Fitri (Evidence Midwifery Journal, 2022)
Diarrhea is a potential endemic disease of Extraordinary Events (KLB) which is often accompanied by death in Indonesia. The nutritional status of children is one of the causes of diarrhea. The purpose of this study was to determine the relationship between nutritional status and the incidence of diarrhea in children. The design of this research is quantitative with case control design. The research site was in Rantau Benuang Village, Rokan Hilir Regency on September 16-30, 2021. The case population in the study was all children aged 6-12 years suffering from 41 children while the control population was children who did not suffer from diarrhea in Rantau Benuang Village, Rokan Hilir Regency in 2021 as many as 218 children. Case samples were taken using total sampling and control samples using systematic random sampling. Data analysis using univariate and bivariate using chi square test. The univariate analysis consisted of 82 respondents. Based on nutritional status, of the 41 case group respondents, there were 28 respondents (68.3%) with poor nutritional status. Of the 41 respondents in the control group, there were 26 respondents (63.4%) with good nutritional status. From all 82 respondents, there were 43 respondents (52.4%) with poor nutritional status. Bivariate analysis showed that there was a relationship between nutritional status (p value = 0.008) and the incidence of diarrhea in children. It is hoped that this final project can be a reference material for health workers in order to provide counseling about diarrhea.